Kematangan Beragama Masyarakat Industri Batik - Tri Astutik Haryati (JURNAL PENELITIAN, 2016)
This article examines the attitudes of society in the Pekalongan batik industry in relation to predictors of confidence based on their perceptions of the pillars of faith and religious activities. Using a quantitative research approach, the results show: first, belief in the pillars of faith influences attitudes by only 10.8%, therefore the result is not significant; second, perception of religious activities influences attitudes by 18.5%, and this result is significant; third, belief in the pillars of faith and perception of religious activities jointly contribute 23.6%, and this result is significant.